Analisis Aktifitas Operasional Shipping Agency PT. Global Triputra Utama Maritim TBK Dalam Mengurus Dokumen Kapal - Muzakky, Ahmad; Sitompul, Mey Krisselni; Putri, Amelia Pratama (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Shipping and port activities require effective ship agency services, particularly in handling ship documentation to ensure smooth operational processes. This study aims to analyze the operational activities and performance of the shipping agency at PT. Global Triputra Utama Maritim Tbk in managing ship clearance documents. The research was conducted through an Internship Program (Practical Work) from October 2025 to January 2026 at Tanjung Balai Karimun. A qualitative descriptive method was employed, with data collected through direct observation, interviews with shipping operational staff, and documentation studies. The results indicate that PT. Global Triputra Utama Maritim Tbk has carried out ship agency functions in accordance with applicable procedures and regulations, including clearance in and clearance out processes involving related institutions such as the Harbor Master and Port Authority (KSOP), Port Health Office, Immigration, Customs, and Navigation authorities. The company’s performance is considered fairly effective in terms of procedural accuracy and inter-agency coordination. However, several constraints affecting operational efficiency were identified, including limited supporting facilities, insufficient operational personnel, delays in document issuance by related institutions, and communication barriers with foreign ship crews. Overall, PT. Global Triputra Utama Maritim Tbk demonstrates good performance in handling ship documentation, although improvements in facilities, human resources, and coordination are required to enhance efficiency and service quality.